Theoretical investigation of stresses induced at blade mounting locations in steam turbine rotor system - Kiran Prasad, Damaria; Ramana, K.V.; Mohan Rao, Nalluri (Zielona Góra: Uniwersytet Zielonogórski)
One of the most common incipient losses of integrity in mechanical structures is the development and propagation of cracks. Especially in rotating members like steam turbine rotors etc. cracks, because of their potential, cause catastrophic failures and are a grave threat to an uninterrupted operation and performance.
Keywords: rotor disc; radial stress; tangential stress; steam turbine rotor